Referred pain: characteristics, possible mechanisms, and clinical management - Jin, Qianjun; Chang, Yuxin; Lu, Chenmiao; Chen, Lunhao; Wang, Yue (Frontiers in Neurology, 2023)
Purpose of Review: Referred pain is a common but less understood symptom originated from somatic tissues. A comprehensive recognition of referred pain is important for clinicians in dealing with pain. The purpose of this study is to summarize current understanding of referred pain, including pathogenesis, characteristics, diagnosis, and treatments. Recent Findings: Referred pain arises not only from pathologies primarily involving the local tissues, but from lesions in distant structures. Central sensitization of convergent neurons and peripheral reflex of dichotomising afferent fibers are two theories proposed to explain the pathological mechanism of referred pain. As syndromes related to referred pain of various origins overlap each other, it is challenging to define referred pain and identify its original lesions. Although various approaches have been used in the diagnosis and treatment of referred pain, including conservative treatments, blockage, radiofrequency, and surgery, management of referred pain remains to be a clinical challenge. Summary: Unlike radicular pain and neuropathic pain, referred pain is a less studied area despite it is common in clinics. Referred pain may be derived from various spinal structures and blockage helps to identify the primary pathology. Due to the heterogeneity in referred pain, treatment outcomes remain uncertain. More studies are needed to further the understanding of referred pain.